Peran Biomarker IL-1β, IL-6, TNF-α, MMP-9, dan SOD dalam Patogenesis Acne Vulgaris: Suatu Tinjauan Literatur - Angelica Vanini Winata Taufiq; Pratiwi Pujilestari Sudarmono; Dian Widiyanti; Harliansyah (STKIP Subang, 2026)
Acne vulgaris is a chronic inflammatory disease of the pilosebaceous unit involving follicular hyperkeratinization, excessive sebum production, Cutibacterium acnes colonization, inflammation, and oxidative stress. The activation of the nuclear factor kappa B (NF-κB) pathway and the inflammasome by C. acnes triggers the release of proinflammatory mediators, such as IL-1β, IL-6, and TNF-α, which contribute to the formation of comedones, papules, pustules, and severe inflammatory lesions. Furthermore, matrix metalloproteinase-9 (MMP-9) plays a role in extracellular matrix degradation, tissue damage, and scarring, while superoxide dismutase (SOD) reflects endogenous antioxidant capacity in response to increased reactive oxygen species (ROS). This review aims to examine the roles of IL-1β, IL-6, TNF-α, MMP-9, and SOD biomarkers in the pathogenesis of acne vulgaris. The method employed is a narrative review conducted through literature searches across PubMed, Scopus, and Google Scholar databases. The findings indicate that IL-1β, IL-6, and TNF-α serve as the primary mediators of acne inflammation. MMP-9 is associated with inflammatory severity, tissue destruction, and scar formation, whereas decreased SOD activity reflects elevated oxidative stress that exacerbates acne lesions. These findings confirm that IL-1β, IL-6, TNF-α, MMP-9, and SOD are critical biomarkers in the pathogenesis of acne vulgaris and possess the potential to be used as parameters for diagnosis, prognosis, and therapeutic evaluation of the condition.